TINJAUAN KRIMINOLOGI TERHADAP SENSUAL MARKETING SEBAGAI STRATEGI PEMASARAN PRODUK YANG DIPERANKAN OLEH SALES PROMOTION GIRL DI KOTA PEKANBARU - Munir, Abdul; Wahyudi, Septian; Zainal, Zainal (UIR PRESS, 2020)
This study tries to describe the phenomenon of exploitation of women's bodies in product marketing business activities (cars and cigarettes) played by SPG in Pekanbaru. The exploitation of the body is a consequence of the product marketing system in the business world through a